2017
DOI: 10.1001/jamapsychiatry.2016.3990
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between the Probability of Autism Spectrum Disorder and Normative Sex-Related Phenotypic Diversity in Brain Structure

Abstract: These findings highlight the need for considering normative sex-related phenotypic diversity when determining an individual's risk for ASD and provide important novel insights into the neurobiological mechanisms mediating sex differences in ASD prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 47 publications
3
62
1
Order By: Relevance
“…Except for acrossgender age differences in group B, no statistically significant differences in age were found between male and female subjects or between ASD and DC subjects. The age bias in group B could be related to the fact that girls are less likely than boys to meet diagnostic criteria for ASD [47,48]. The inter-rater reliability of manual segmentation labels is reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Except for acrossgender age differences in group B, no statistically significant differences in age were found between male and female subjects or between ASD and DC subjects. The age bias in group B could be related to the fact that girls are less likely than boys to meet diagnostic criteria for ASD [47,48]. The inter-rater reliability of manual segmentation labels is reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This study was cross‐sectional, specific to high functioning males with ASD, lacked pubertal developmental measures [Urosevic et al, ] and did not include a semi‐structured clinical interview of possible psychiatric comorbidity such as the SCID‐5‐RV. Hence, our findings describe age‐related differences that may not generalize to others within the autism spectrum, including females [Craig et al, ; Ecker et al, ; Wilson et al, ]. However, study strengths include the relatively large sample of physically healthy, medication naive, clearly diagnosed males with ASD without confounding psychiatric diagnoses and matched controls, and the 25 year age span from childhood to adulthood.…”
Section: Limitationsmentioning
confidence: 86%
“…The result of fewer female participants is that the observed findings of brain structure associated with ASD may not generalise to females (Lai et al, 2015). In fact, studies have demonstrated differences in brain structure based on gender, including altered GMV (Subbaraju et al, 2015), cortical thickness (Ecker et al, 2017), increased temporal WMV/GMV and reduced cerebellar volume (Bloss and Courchesne, 2007), increased amygdala volume (Schumann et al, 2009), increased WMV/GMV volume (Beacher et al, 2012) and reduced gyrification (Schaer et al, 2013) in girls with autism relative to boys. This will necessitate collecting sufficient data for females with ASD, in order to achieve accurate estimates of gender differences in brain structures.…”
Section: Discussionmentioning
confidence: 99%